RESEARCH ON UNBALANCING FORCE APPROACH OF THE GEOTECHNICAL CENTRIFUGE BASED ON PRETENSION MEASUREMENT OF BOLTS - CHEN Hongyong; NIU Hongpan; LI Qisheng; YANG Yuming; SONG Qiong; LI Xinyao (Jixie qiangdu)
An online measurement method of a dynamic unbalance force of the geotechnical centrifuge was carried out based on monitoring the change of the axial preload of anchor bolts. Firstly, the change model of the axial preload of the anchor bolt under different unbalanced force states was deduced theoretically, which proved the feasibility of indirectly measuring the unbalanced force of the centrifuge. Then, the typical testing case was carried out on the TLJ-500 centrifuge, and the law of the dynamic unbalance moment changing with the counterweight was obtained. By fitting the change of the axial force at the measuring point, the relation between the axial force at the measuring point and the unbalance mass and the running gravitational acceleration g value of the centrifuge was established.Finally, the relation between the change of the axial preload of anchor bolts, acceleration of the centrifuge and counterweight mass were obtained by measuring the preload change of one anchor bolt and fitting the response surface. The results show that it is feasible to obtain the unbalanced force of the centrifuge operation by monitoring the change of anchor bolts’ pre-tightening force， and the centroids of different counterweights should be kept consistent in the test. When calculating the counterweight mass to balance the rotating arm according to the fitting formula, a larger acceleration should be used as far as possible to reduce the error caused by the centrifuge not being leveled.